Exercise and outcomes in macrosomic pregnancies. (2nd December 2021) - Bulut, Ayca Nazli; Ceyhan, Venhar; Demir, Mustafa Bertan; Ak, Mehmet; Dolanbay, Mehmet
Abstract: Objective: Pregnancy is generally known to be a period when physical activity is partially or totally restricted to avoid negative outcomes such as miscarriage or premature birth. The aim of this study was to evaluate the effect on maternal and fetal outcomes of exercise in pregnancies complicated by macrosomia. Material and Method: In this retrospective study, the data were retrospectively screened of women who gave birth at ≥38 weeks with infant birthweight of ≥4000 gr. The patients were separated into two groups as those who followed an exercise program of walking regularly for 30–60 mins at least 1 day a week throughout pregnancy and those who did not. The maternal and fetal complications were compared between the groups. A total of 252 patients were included in the study as 84 women who exercised during pregnancy and 168 women selected at random in the ratio of 2:1 who did not exercise. Results: When the gestational week at birth was examined, a statistically significantly higher rate of patients in the non-exercise group gave birth at ≥40 gestational weeks. Although not at a statistically significant level, maternal and fetal complications were observed more in the non-exercise group. Conclusions: The results of this study showed that excessive maternal weight gain was statistically significantly reduced, and although not at a statistically significant level, maternal and fetal trauma were reduced in macrosomic pregnancies with regular exercise. As recommended by ACOG, for pregnant women at risk of macrosomic fetus, exercise of walking for 30–60 mins several days a week will have positive effects on both the mother and infant.